Fintech : A Literature Review - bhenu Arha; Ali Jufri (Jurnal Proaksi, 2020)
The development of the startup business that continues to increase every year makes startups competing to introduce their products to the public. One that is currently increasing rapidly is Fintech (Financial Technology). The emergence of Fintech in Indonesia aims to facilitate the public in conducting financial transactions online, increase financial literacy, and realize financial inclusion. This mapping study aims to identify previous research on fintech and suggest future research. This study uses a systematic literature review (SLR), which is to collect and assess available research related to the subject of interest, so as to achieve an impartial outcome that can be audited and repeated. This study uses 22 articles identified from electronic databases / sources. Fintech is expected to strike the right balance between providing consumer protection and maintaining financial stability while simultaneously providing sufficient incentives for Fintech's innovation. It is able to build social construction, previous studies have attracted regulators and lawmakers, entrepreneurs, and investors who participated in technology applied in the area of ??innovative financial services. Keywords : Financial Technology and Literatur Review